(untitled) (Global Journal of Science Frontier Research, 2016)
The Antibacterial effects of Phyllanthus discoideus and Terminalia avicennioides on Methicillin resistant Staphylococcus aureus were studied. Three hundred and twenty four (324) samples were collected from the skin, boil and wound of pupils in twelve (12) selected primary schools in Ekiti State, they were inoculated by streaking on to dried mannitol salt agar plates. Staph aureus was identified by agar diffusion method using methicillin disc. Susceptibility testing of the methicillin resistant Staphylococcus aureus to the crude extracts of the leaves of Phyllanthus discoideus and Terminalia avicennioides, was carried out at various concentrations((10 to100mg/ml).Out of the 324 isolates, 151 (47%) were methicillin resistant and 118 (78%)) were susceptible to P. discoideusextract in 151 MRSA isolates, while the remaining 33MRSA isolates were resistant. 121 MRSA isolates were susceptible to T. avicennioides extract, 30 were resistant to the extract, the percentage susceptible was 80%. The susceptibility of MRSA isolates to the leave extracts of the two plants was very high,it shows that the crude extracts from the leave of these plants could be used as therapies for the treatment of diseases that are associated with methicillin resistant staphylococcus aureus.